PREVENTION OF CRIMES AGAINST THE SEXUAL INVIOLABILITY OF MINORS THROUGH THE USE OF THE INTERNET - Urakov Dzhahongir Rajabovich (Scholar Express Journals, 2023)
The article analyzes the problem of crimes committed against the sexual inviolability of minors through the use of the internet. The actions of underage internet users, making them pay attention to this factor of work, and the type of crime in question is determined by measures to prevent victims
Keywords: internet; juvenile; crimes against sexual immunity; cyberbullying